Ecophysiology and Comparative Genomics of Nitrosomonas mobilis Ms1 Isolated from Autotrophic Nitrifying Granules of Wastewater Treatment Bioreactor - Thandar, Soe Myat; Ushiki, Norisuke; Fujitani, Hirotsugu; Sekiguchi, Yuji; Tsuneda, Satoshi (Frontiers in Microbiology, 2016)
Ammonia-oxidizing bacteria (AOB), which oxidize ammonia to nitrite in the first step of nitrification, play an important role in biological wastewater treatment systems. Nitrosomonas mobilis is an important and dominant AOB in various wastewater treatment systems. However, the detailed physiological and genomic properties of N. mobilis have not been thoroughly investigated because of limited success isolating pure cultures. This study investigated the key physiological characteristics of N. mobilis Ms1, which was previously isolated into pure culture from the nitrifying granules of wastewater treatment bioreactor. The pure culture of N. mobilis Ms1 was cultivated in liquid mineral medium with 30 mg-N L-1 (2.14 mM) of ammonium at room temperature under dark conditions. The optimum growth of N. mobilis Ms1 occurred at 27°C and pH 8, with a maximum growth rate of 0.05–0.07 h-1, which corresponded to a generation time of 10–14 h. The half saturation constant for ammonium uptake rate and the maximum ammonium uptake rate of N. mobilis Ms1 were 30.70 ± 0.51 μM NH4+ and 0.01 ± 0.002 pmol NH4+ cells-1 h-1, respectively. N. mobilis Ms1 had higher ammonia oxidation activity than N. europaea in this study. The oxygen uptake activity kinetics of N. mobilis Ms1 were Km(O2) = 21.74 ± 4.01 μM O2 and V max(O2) = 0.06 ± 0.02 pmol O2 cells-1 h-1. Ms1 grew well at ammonium and NaCl concentrations of up to 100 and 500 mM, respectively. The nitrite tolerance of N. mobilis Ms1 was extremely high (up to 300 mM) compared to AOB previously isolated from activated sludge and wastewater treatment plants. The average nucleotide identity between the genomes of N. mobilis Ms1 and other Nitrosomonas species indicated that N. mobilis Ms1 was distantly related to other Nitrosomonas species. The organization of the genes encoding protein inventory involved in ammonia oxidation and nitrifier denitrification processes were different from other Nitrosomonas species. The current study provides a needed physiological and genomic characterization of N. mobilis-like bacteria and a better understanding of their ecophysiological properties, enabling comparison of these bacteria with other AOB in wastewater treatment systems and natural ecosystems.